Comparative investigation on three laboratory testing methods for short-term aging of asphalt binder. (10th January 2021) - Tian, Yu; Li, Hui; Zhang, Hengji; Yang, Bing; Zuo, Xin; Wang, Hanbing
Highlights: Evaluate rheological and chemical properties of asphalt during short-term aging. The aging of modified asphalt includes polymer degradation and asphalt oxidation. There are certain differences in the effects of three short-term aging methods. 5 h PAV can be regarded as an alternative short-term aging method for TFOT or RTFOT. Abstract: As one type of organic binder, asphalt is prone to aging under climatic conditions such as temperature, oxygen, water, sunlight, etc., which is one of the principal factors causing the performance degradation (raveling, potholes, cracking) of asphalt pavement. In addition to long-term aging, short-term aging of asphalt binder will also have an important impact on the performance of asphalt pavement. As the most commonly used short-term aging methods, the Thin Film Oven Test (TFOT) and Rolling Thin Film Oven Test (RTFOT) still have some problems to be studied, such as the convenience of test operation, the difference of aging degree between them and whether they can be applied to a wide variety of polymer modified asphalt binders. Some scholars have proposed that the aging effect of the 5 h Pressurized Aging Vessel (5 h PAV) test is equivalent to RTFOT, which can be used as an alternative to each other. However, this is limited to preliminary verification and lacks sufficient proof. Therefore, three types of short-term aging methods (TFOT, RTFOT and 5 h PAV) were carried out for four types of asphalt binders at first in this paper. Then, Dynamic Shear Rheometer (DSR), Fourier Transform Infrared Spectroscopy (FT-IR) and Gel Permeation Chromatography (GPC) were used to carry out the comprehensive macroscopic rheological and micro chemical evaluation of asphalt samples before and after aging, and compare the aging effect of different short-term aging processes. Finally, it is concluded that 5 h PAV can replace TFOT for 70# asphalt and RTFOT can be replaced by 5 h PAV for modified asphalt. It is of great significance to improve the convenience of asphalt short-term aging test and explore the aging method of asphalt mortar.